Lees, Clare A. & Gillian R. Overing 2001: Double Agents: Women and Cerical Culture in Anglo-Saxon England - Klinck, Anne L. (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen